2021
DOI: 10.11604/pamj.2021.39.179.29354
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal dialysis in Tunisia: complications, technique and patient´s survival (twenty-seven years of experience in a single center)

Abstract: Introduction peritoneal dialysis (PD) is a renal replacement therapy method that offers various advantages to end-stage renal disease patients. The aim of our study was to analyze patient characteristics, peritonitis and clinical outcome over a 27-year period of PD in our center. Methods retrospective study of incident patients on PD from January 1990 to December 2017. A total of 304 patients were enrolled in the study group. All patients over 15 years of age entering t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
3
0
0
Order By: Relevance
“…We can speculate that, because of hypertension, patients tend to pay more attention to their health and learn more health-related knowledge and solutions than the other respondents, thus lowering the chance of contracting peritonitis. The results of this research are similar to those reported by Salem et al (2021).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We can speculate that, because of hypertension, patients tend to pay more attention to their health and learn more health-related knowledge and solutions than the other respondents, thus lowering the chance of contracting peritonitis. The results of this research are similar to those reported by Salem et al (2021).…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, the longer the PD time and the more mature the technology, the more likely PD failure, and peritonitis infection can be reduced. This result is similar to the ndings of Salem et al ( 2021), who studied PD patients in Tunisia [15]. The results indicate that new PD patients should strengthen their knowledge about the technical operation of PD work by regularly attending teaching activities.…”
Section: Discussionsupporting
confidence: 90%
“…Over the years, there was a change in the causative microorganism profile: predominance of gram-negative bacilli between 1996 and 2000, then the emergence of gram-positive cocci with a constant progressive rise from 2001 till 2017. Such findings of the predominance of gram-positive bacteria were similar to studies conducted in Scotland, Canada, the United States of America, and Hong Kong in which gram-positive microorganisms comprised up to 66% of causative pathogens of peritonitis (19).…”
Section: Incidence and Clinical Outcomes Of Peritonitissupporting
confidence: 84%